PENGEMBANGAN KARIR GURU - Lelyana Pasaribu (UNIVERSITAS BENGKULU, 2020)
This research described how career development teacher SMK Negeri 3 Seluma. Specifically this research 1) described teacher’s assignment system according to functional position, 2) described teacher’s empowerment effort to be promoted, 3). to describe teacher promotion sistem. The method used in this research is descriptive qualitative. The conclusion of this research that teacher career development at SMK Negeri 3 Seluma in improving teacher professionalism has been done well, where the principal democratically provides opportunities for teachers to develop the potential in a career to be promoted.